Novel chromatic technique based on optical absorbance in characterizing mineral hydraulic oil degradation - Ossia, C.V.; Kong, H. (Hindawi Publishing Corporation, 2012)
A low cost, compact, real-time, and quick measurement optical device based on the absorbance of white light, which comprised of photodiodes in a 3-element color-sensor, feedback diodes, water and temperature sensing element, and so on, was developed and tested in low absorption mineral oil. The device, a deviation from conventional electrical, mechanical, and electrochemical techniques, uses color ratio (CR) and total contamination index (TCI) parameters based on transmitted light intensity in RGB wavelengths for oil condition monitoring. Test results showed that CR corroborated CIE chromaticity (X - Y Coordinates) and increased with oil degradation unlike Saturation S and Hue H. CR was found to be independent of the particulate contaminants of oil, but dependent on chemical degradation. TCI depended on both chemical degradation and particulate contaminants in oil, being most sensitive in the blue wavelength range and least in the green. Furthermore, results agreed with those of viscometry, total acid number (TAN), and UV-VIS photospectrometry. CR and TCI gave clearer indication of oil degradation than key monitoring parameters like TAN and were found to be effective criteria for characterizing the degradation of hydraulic mineral oils. ？ Copyright 2012 C. V. Ossia and H. Kong.